Stability of a circular ring in postcritical equilibrium states with two deformation-dependent loads and geometrical imperfections - Kozák, Imre; Szabó, Tamas (Computer Assisted Methods in Engineering and Science, 2023)
The circular ring is linearly elastic and its cross-section is rectangular. Two deformation dependent distributed loads, that is follower loads, are applied simultaneously on the outer surface of the ring. The first load is a uniform pressure on the whole outer surface. The second load is uniform normal traction exerted on two surface parts situated in axially symmetric positions. Both loads are selfequilibrated independently from each other. A nonlinear FE program with 3D elements is used for the numerical analysis of a geometrically perfect and two imperfect rings. Displacement control is used in the equilibrium iterations. Equilibrium surfaces are determined in the space of three parameters such as one characteristic displacement coordinate, and two load factors. The stability analysis is performed in the knowledge of the equilibrium surfaces.